Features of the Application of Innovative Means in the Process of Teaching a Foreign Language to Children with Speech Difficulties - Pavliuk, Roman; Tymchenko, Iryna (Educological discourse, 2026)
The article considers the problem of forming communicative competence of primary school pupils with speech difficulties in an inclusive educational environment. In particular, the emphasis is on the difficulties that children with special educational needs (SEN) face when learning a foreign language, as well as on the importance of introducing innovative technologies into the educational process. An analysis of scientific approaches to studying the peculiarities of foreign language acquisition by children with special educational needs, particularly those with speech difficulties, is presented. The effectiveness of using interactive platforms, mobile applications, project activities, game methods, etc. as innovative means of teaching a foreign language to children with speech difficulties is substantiated. The study presents a qualitative and quantitative analysis of a questionnaire survey conducted among primary school English teachers working with children who have special educational needs. The survey allowed the authors to study the features of the use of innovative technologies in teaching a foreign language to children with speech difficulties, the ability and willingness of teachers to implement innovative technologies in the educational process for children with SEN, to identify the difficulties that teachers face when using innovative technologies in foreign language lessons, and to study the effectiveness of using such technologies in the process of forming foreign language communicative competence of primary school pupils with speech difficulties. The study results demonstrated the high effectiveness of using innovative, interactive technologies in teaching a foreign language to primary school children with speech difficulties. Among them, the respondents identified the following: role-playing games, visualisations, and online resources. At the same time, the survey enabled the authors to identify several challenges that teachers encounter when teaching a foreign language to children with speech difficulties, including a lack of time, inadequate methodological support, insufficient collaboration with speech therapists, and the need for ongoing professional development. Based on the analysis of the survey results, the authors developed methodological recommendations for the use of innovative teaching aids in teaching a foreign language to primary school pupils with speech difficulties.